Hydrodynamic gene delivery of CC chemokine binding Fc fusion proteins to target acute vascular inflammation in vivo. - McNeill, E; Iqbal, A; White, G; Patel, J; Greaves, D; Channon, K (Nature, 2015)
Blockade of CC chemokines is an attractive yet under utilized therapeutic strategy. We report the in vivopharmacokinetics of a broad-spectrum vaccinia virus CC chemokine binding protein (35 K) fused to human IgG1 Fc. We demonstrate that the in vivoefficacy of the protein can be interrogated using hydrodynamic gene delivery of a standard mammalian expression plasmid. High plasma levels of the 35 K-Fc protein are maintained for at least 14 days post gene transfer, with the protein still detectable at 5 weeks. We confirm that the protein has biological activity in acute inflammation, causing a significant reduction in monocyte recruitment during zymosan induced peritonitis. The ability of 35 K-Fc to block more complex pathologies is demonstrated using aortic digests to assess angiotensin II mediated leukocyte recruitment to the aorta. Angiotensin II causes upregulation of mCCL2 in the aorta causing the accumulation of CCR2+cells. Peak monocyte recruitment to the aorta occurs within 3 days and this process is CC chemokine dependent, being significantly reduced by hydrodynamic delivery of 35 K-Fc.